(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
As usual, we analyze in this Chronica the Iberian inscriptions published or revised during the years mentioned in the title, excepting those published in Palaeohispanica. We also include other inscriptions and reinterpretations published previously but not included in the previous chronicle.